RFID based Security System for Visitors in a Gated Area - et. al., Preeti Singh Nirmale, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The requirement for cutting edge Security systems has always been in demand. A low cost and reliable system ispreferred by every customer. With the world facing the pandemic due to a deadly virus which is spreading by touch, it becomes more important to rely on touchless technology. This project focuses on the key aspect that the prevention of an unwarranted activity in a campus can be avoided if the visitors in-time and out-time is checked and documented. And can be compared if a pattern of activity is followed by the visitor. Most of the campuses rely on an old system of pen paper or the more recent app-based permission, BUT none of them really check on the amount of time spent by a visitor inside the campus, à did the visitor leave after meeting the host? The increasing need for safety and prevention checklist for visitors in a gated area is the key aspect of the project.